The use of effective microorganisms (EM) to remove filter cake in a dynamic condition [electronic resource] - Md. Hairudi Jani, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malayasia, 2010